Acute Fasting Does Not Induce Cognitive Impairment in Mice - Zheng, Hua; Ton, Hoai; Yang, Lei; Liufu, Ning; Dong, Yuanlin; Zhang, Yiying; Xie, Zhongcong (Frontiers in Neuroscience, 2019)
Preoperative baseline cognitive impairment is associated with postoperative neurocognitive disorder (PND). Fasting, and more generally, calorie restriction has been shown to exert controversial effects in clinical settings and various animal models of neurological disorders. Every patient needs acute fasting before anesthesia and surgery. However, the impact of acute fasting on cognitive function remain largely unknown. We, therefore, set out to determine whether acute fasting can induce neurotoxicity and neurobehavioral deficits in rodents. In the present system establishment study, a mouse model of acute fasting was established. The effects of the acute fasting on natural and learned behavior were evaluated in the buried food test, open field test and the Y maze test. The expression of c-Fos, the marker of neuronal activation, and caspase-3 activation, the marker of cellular apoptosis, were measured with immunohistochemistry. We found that the 9 h acute fasting increased the latency to eat food in the buried food test. The acute fasting also selectively increased the total distance and decreased the freezing time in open field test, and increased the duration in the novel arm in the Y maze test. Besides, the immunohistochemical study showed that the fasting significantly increased the c-Fos level in the hippocampus and various sub-cortical areas, including paraventricular thalamus (PVT), dorsomedial hypothalamus (DMH), lateral hypothalamus (LH), and basal amygdala (BMA). However, the acute fasting did not induce apoptosis, demonstrating by no appearance of caspase-3 activation in the corresponding brain areas. These data showed that acute fasting did not cause cellular apoptosis and cognitive impairment in the mice. Instead, the acute fasting increased the neuronal activity, enhanced the ambulatory activity and improved the spatial recognition memory in the mice. These findings will promote more research in the established system to further determine the effects of perioperative factors on the postoperative neurocognitive function and the underlying mechanisms.